Dynamics of a system comprising a pre-stressed orthotropic layer and pre-stressed orthotropic half-plane under the action of a moving load - Akbarov, Surkay; Ilhan, Nihat (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper investigates the dynamic response to a moving load of a system comprising an initially stressed covering layer and initially stressed half-plane, within the scope of the piecewise-homogeneous body model utilizing three-dimensional linearized wave propagation theory in the initially stressed body. It was assumed that the materials of the layer and half-plane are anisotropic (orthotropic), and that the velocity of the line-located moving load is constant as it acts on the free face of the covering layer. The investigations were made for a two-dimensional problem (plane-strain state) under subsonic velocity of the moving load for complete and incomplete contact conditions. Corresponding numerical results were obtained for the stiffer layer and soft half-plane system in which the modulus of elasticity of the covering layer material (for the moving direction of the load) is greater than that of the half-plane material, which was assumed to be isotropic. Numerical results are presented and discussed for the critical velocity and stress distribution for various values of the problem parameters. In particular, it was established that, the critical velocity of the moving load is controlled mainly with a Rayleigh wave speed of a half-plane material and the initial stretching of the covering layer causes to increase these values. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: orthotropic material; critical velocity; dynamic response; initial stress; covering layer; half-plane moving; load; Mechanics